Multimodality Imaging in the Diagnosis and Assessment of Cardiac Amyloidosis - Velaga, Jyothirmayi; Liew, Charlene; Choo Poh, Angeline Choo; Lee, Phong Teck; Lath, Narayan; Low, Shoen Choon; Bharadwaj, Pushan (World Journal of Nuclear Medicine, 2022)
Amyloidosis is a rare disorder where abnormal protein aggregates are deposited in tissues forming amyloid fibrils, leading to progressive organ failure. Although any organ can be affected, cardiac involvement is the main cause of morbidity and mortality associated with amyloidosis as diagnosis is often delayed due to the indolent nature of the disease in some forms. An early diagnosis of disease and knowledge of the type/subtype of cardiac amyloidosis (CA) are essential for appropriate management and better outcome. Echocardiography is often the first line of investigation for patients suspected of CA and offers superior hemodynamic assessment. Although cardiovascular magnetic resonance (CMR) imaging is not diagnostic of CA, it provides vital clues to diagnosis and has a role in disease quantification and prognostication. Radiolabeled bone seeking tracers are the mainstay of diagnosis of CA and when combined with screening of monoclonal light chains, bone scintigraphy offers high sensitivity in diagnosing transthyretin type of CA. This review aims to describe the noninvasive imaging assessment and approach to diagnosis of patients with suspected CA. Imaging features of echocardiography, nuclear scintigraphy, and CMR are described with a brief mention on computed tomography.
Keywords: cardiac amyloidosis; strain imaging; bone scintigraphy; 99mTc pyrophosphate (PYP); cardiac magnetic resonance; T1 mapping; late gadolinium enhancement; extracellular volume fraction; myocardial strain; cardiac computed tomography